1983
DOI: 10.1159/000123524
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Differentiation of Social Play in Rat Pups Is Mediated by the Neonatal Androgen-Receptor System

Abstract: Social play in juvenile rats, like that in several primate species (including humans), is sexually dimorphic. Males initiate and become involved in more play-fights than do their female peers. The play-fighting of female pups can be masculinized by neonatal exposure to either testosterone or 5α-dihydrotestosterone, suggesting that in the rat the masculinization of social play is mediated by the androgen-receptor system. In this paper we present evidence that further supports this hypothesis. In the first study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
80
3
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(85 citation statements)
references
References 16 publications
1
80
3
1
Order By: Relevance
“…The roles of these hypothalamic nuclei in reproductive behavior are not completely understood, but the VMN appears to be involved in the lordosis response in female rats (17), and the SDN-POA has been implicated in the execution of coital behavior in male rats (16). Some aspects of sexual differentiation of the brain, including the development of sexually dimorphic patterns of social play, appear to be regulated by the direct actions of androgens in the brain, rather than by the aromatization of androgens to estrogen (18). A similar process of sexual differentiation appears to occur in the brains of all mammalian species including humans.…”
Section: Role Of Hormones In Brain Development and Cognitionmentioning
confidence: 99%
“…The roles of these hypothalamic nuclei in reproductive behavior are not completely understood, but the VMN appears to be involved in the lordosis response in female rats (17), and the SDN-POA has been implicated in the execution of coital behavior in male rats (16). Some aspects of sexual differentiation of the brain, including the development of sexually dimorphic patterns of social play, appear to be regulated by the direct actions of androgens in the brain, rather than by the aromatization of androgens to estrogen (18). A similar process of sexual differentiation appears to occur in the brains of all mammalian species including humans.…”
Section: Role Of Hormones In Brain Development and Cognitionmentioning
confidence: 99%
“…Although estradiol is critical for masculinization of some behaviors in the perinatal rat, others are affected specifically by androgens during the neonatal period. Play is organized by the perinatal interaction of androgens with the AR (Meaney et al 1983;Meaney and McEwen 1986;Pellis and Pellis 1997). Although limited examples of androgen organization of behavior exist in the rat, it appears to be more common in the nonhuman primate (Cooke et al 1998;Hines 1992).…”
Section: Role Of Androgens In Reproductive and Behavioral Developmentmentioning
confidence: 99%
“…However, some behaviors, such as rough-and-tumble play, are specifically organized by androgens. The critical time in the rat for organization of play is the early neonatal period, when interactions of androgens with the AR set up the sex difference observed in juveniles (Meaney et al 1983;Meaney and McEwen 1986;Pellis and Pellis 1997). Studies have shown that increased male rough-and-tumble play is specifically organized by the stimulation of ARs in the amygdala region of the brain (Meaney et al 1983) and is not dependent on activational effects of steroids (Meaney and McEwen 1986).…”
Section: Effect Of Androgen-active Chemicals On Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Play fighting is decreased in male rats castrated at birth and its frequency begins to decline at the onset of puberty (Beatty et al, 1981;Meaney, 1988;Pellis and Pellis, 1990). Analysis of Tfm male rats suggests that ARs are involved in the development of play fighting behavior since, as juveniles, Tfm males show decreased play fighting behavior compared to wt males (Meaney et al, 1983;Meaney, 1988), although recent data suggest that this difference may depend on the testing paradigm (Field et al, 2006). Tfm males also fail to show the male-typical decline in playful attack with age, but like wt males they do show a decline in some aspects of playful defense, indicating that ARs are involved in some but not all aspects of play fighting (Field et al, 2006).…”
mentioning
confidence: 99%